К истории проекта создания «Христианского музея» в Херсонесе - Шаманаев, А.В. (Херсонесский сборник, 2006)
Вклад Одесского общества истории и древностей в дело изучения и сохранения херсонесских древностей хорошо известен и многократно рассматривался в научной литературе (Гриневич 1927: 12; Сорочан, Зубарь, Марченко 2000: 23–25; Тункина 2002: 530–533). Практически со времени создания в 1839 г. это общество проявляло постоянный интерес к Херсонесу, а с 1876 по 1886 г. им осуществлялись раскопки городища. Одним из интересных фактов деятельности ООИД является проект создания «Христианского музея» на территории городища. The article is devoted to the history of the project “Christian museum” in Chersonesos. The interesting situation was at this site in the middle of XIX c.: the artifacts of the Ancient time were transferred to Hermitage (St. Petersburg) or Museum of Odessa Society of History and Antiquities, but the Middle Ages’ finds were left in Sevastopol. In 1850 Archbishop of Cherson and Taurida Innokentiy started the program of restoration of the Christian monuments in Crimea. Among them the museum in Chersonesos was in this plan. But the project was stopped by the Crimean War (1853-1856).